Urgensi Ijtihad Saintifik dalam Menjawab Problematika Hukum Transaksi Kontemporer - Fauzi M (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2011)
This article will discuss abaout the rational urgency to do scientific ijtihad to answer the legal issues of contemporary transaction and also perform scientific ijtihad basis and examples of scientific ijtihad in answering legal issues of contemporary transactions.